“Un-American Confessions”: Translation as Subversion in Robert Lowell’s Life Studies (1959) - Simon Van Schalkwyk (European Journal of American Studies)
This article argues that Robert Lowell’s employment of techniques of poetic "imitation" - a liberal form of translation - during the composition of the Life Studies poems allows him to simultaneously stage and to conceal his reliance upon foreign poetic sources. Lowell’s Life Studies imitations thus represent an attempt to “cover-up” poetic collusions with foreign sources at a time when cold war “containment culture” and the specter of McCarthyism threatened to render any such collusion increasingly suspect, if not entirely “Un-American.” The Life Studies imitations, by this account, offer furtive testimony to Lowell’s potentially subversive poetic preoccupation and engagement with cold war cultural anxieties circulating around terms such as containment, conspiracy, domesticity, paranoia, security, secrecy.